A Methodology for Rapid Assessment of Rural Transport Services - Starkey, Paul (World Bank, Washington, DC, 2014)
Rural transport services are often inadequate. Passenger and goods transport needs improving to stimulate rural economies and reduce poverty. Understanding existing rural transport systems and constraining factors is a precondition for appropriate policy action. The Sub-Saharan Africa Transport Policy Program (SSATP) commissioned a study to develop and test a methodology for the rapid assessment of rural transport systems. The guidelines specified passenger and freight transport for distances of 5-200 km, encompassing much rural transport, but excluding within-village transport, long-distance national transport and international corridors. Rural transport systems operate on hub and spoke systems at several levels. Key rural hubs are provincial/regional towns, market/district towns and villages. The various spokes and hubs have characteristic combinations of transport, including trucks, buses, minibuses, pickups and intermediate means of transport (IMTs). The smallest spokes are footpaths while national spokes form transport corridors. The methodology surveys transport types, operators, users and regulators at sampled hubs and spokes, stratified by hub hierarchy and remoteness. This provides a rapid overview of rural transport systems, highlighting key constraints, stakeholder views and proposals for improvements. This document contains practical advice relating to local observations, interview techniques, survey opportunities and traffic counts. Illustrative data forms and check lists of possible topics are provided, for modification according to local needs.